Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1080/10640266.2018.1453632
|View full text |Cite
|
Sign up to set email alerts
|

“They don’t really get heard”: A qualitative study of sibling involvement across two forms of family-based treatment for adolescent anorexia nervosa

Abstract: Little is known about the involvement of siblings in family-based treatment (FBT) for anorexia nervosa (AN). To explore the experience of families, adolescents who had completed FBT, their siblings, and parents were interviewed. Siblings reported that involvement in FBT enhanced their understanding of anorexia and that they supported their family in various ways. While siblings often wished they had attended more sessions, there was no consensus among parents and patients regarding sibling attendance and many … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 13 publications
1
22
0
Order By: Relevance
“…The reviewed studies indicated that the changes in family relationships and everyday life brought about a change in non-ED siblings' perceived roles in the family as well. As reported in several qualitative studies, non-ED siblings commonly assumed responsibility over their siblings' health and well-being, especially when they were the older siblings (25,32,43,46). Non-ED siblings described a dual and at times conflicting role, in which they were both supporters of the diagnosed siblings and the caring parents' collaborators (25,31,32).…”
Section: Siblings' Family Rolementioning
confidence: 94%
See 4 more Smart Citations
“…The reviewed studies indicated that the changes in family relationships and everyday life brought about a change in non-ED siblings' perceived roles in the family as well. As reported in several qualitative studies, non-ED siblings commonly assumed responsibility over their siblings' health and well-being, especially when they were the older siblings (25,32,43,46). Non-ED siblings described a dual and at times conflicting role, in which they were both supporters of the diagnosed siblings and the caring parents' collaborators (25,31,32).…”
Section: Siblings' Family Rolementioning
confidence: 94%
“…Guilt was also a prominent emotion among non-ED siblings. Some felt responsible for the onset of the ED due to their past remarks or actions, some blamed themselves for not helping their siblings as much as they could, and for some the split loyalty, to their patents on one hand and to their siblings on the other, evoked a persistent sense of guilt (25,31,32,43,46). Moreover, in-depth interviews with non-ED siblings revealed a sense of grief and sacrifice, as well as a feeling they lost their family, their normal childhood, their good relationship with their sibling, and their individual identity (32,42,43).…”
Section: Mental Health and Well-being Among Siblings Of Individuals Wmentioning
confidence: 99%
See 3 more Smart Citations